(untitled) (EAAE Annual Conference Proceedings, 2019)
On this annual EAAE meeting I would like to talk about and explain an initiative that has been taking place on our campus for three academic years now because I think it fits the theme of the EAAE meeting 2019 ‘Hidden School’ so well and is worth mentioning because it might inspire other European Architectural Institutes to organize a similar event. It is so easy to do and we notice it has meant so much to our students already. It is called TAXI. TAXI — phonetically the same in every language — is an ephemeral drive to any destination, taken from point A to B, driven by a myopic view ignoring the whole. Through specific focus a guest will take us on a tour with insights that are possibly fun, serious or interesting. This weekly-Thursdaysmidday gathering intends to expand or explore anybody’s frame of reference. The weekly (really meaning weekly...) TAXI, a collaboration with student association Modulor, contributes to broadening and deepening the frame of reference of the students by inviting guests (teachers, students, international relations...) to come and talk briefly, not about their work, but about their own fascinations and inspiration. The initiative resulted from a team meeting of our Architecture department: one of the studio teachers mentioned the systematic lack of reference framework among students. I responded that maybe it was up to us, professors, to show them some examples of what we mean by that. Together with young studio teachers Steven Schenk and Wannes Peeters we brainstormed about a suitable format to do so.